International Mobility, Erotic Plasticity and Eastern European Migrations. - Cvajner, Martina (Migration Letters, 2019)
When individuals cross a border and settle in a new social environment, they become migrants. People come here to work, improve the family conditions, restore a lost status. They work, send remittances, strive to adjust their legal status, learn how to cope with a new way of living. But they also make new friends, new lovers, reunite families. They also encounter new sexual cultures, new erotic narratives and norms. Migration is consequently a good test for contemporary theories of erotic plasticity. Are adult migrants, that have acquired and practised for decades a given erotic habitus, able to change it in depth during emigration? And which are, if any, the dimensions of these change? Eastern European women pioneers in Italy – women who have migrated alone, outside of any recruitment program, to areas with no previous history of immigration from their lands – provide a fascinating case of sexual change.